Pengaruh Career Planning, Work Stress, Workplace Well Being terhadap Turnover Intention pada Karyawan Hotel Bintang Tiga Puncak Cipanas - Abyan Arfari Nursi; Beta Beta Oki Baliartati; Wiwik Robiatul Adawiyah; Dita Oki Berliyanti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of this study was to analyze the effect of Career Planning, Work Stress, Workplace Well Being on Turnover Intention of Three Star Hotel Employees Puncak Cipanas. The independent variables in this study are Career Planning, Work Stress, Workplace Well Being and the dependent variable in this study is turnover intention. Data were collected from 100 respondents using sensus. The technique used to analyze this research is hypothesis testing using multiple linear regression methods with the SPSS assistance program version 21. The results of hypothesis testing in this study showed that there was a negative effect of Career Planning on Turnover Intention, a positive effect of Work Stress on Turnover Intention, and a Workplace Well Being on Turnover Intention. The managerial implication in this study is to reduce the Work Stress variable, so that it does not have an impact on Turnover Intention or has a small effect on Turnover Intention, management can still maintain good relations with employees and reduce employee workload so it does not cause Work Stress.